Relationship between Fear of Pain and Movement among Stroke Patients with Poor Coordination: Relationship between Fear of Pain and Movement - Mansoor, Amna; Munawar, Arooj; Touqeer, Sana; Ahmed, Taimoor; Umer, Aiman (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
Stroke is a major cause of long-term disability worldwide, often leading to motor impairments and reduced coordination. Beyond physical limitations, many stroke survivors experience psychological barriers such as fear of pain and movement, which can further hinder rehabilitation progress. Objectives: To determine the relationship between fear of pain and movement among stroke patients with poor coordination. Methods: This cross-sectional correlational study was conducted over four months at Ganga Ram Hospital, Lahore, involving 189 ischemic stroke patients aged 45–85 years, selected via convenience sampling. The Fear-Avoidance Beliefs Questionnaire (FABQ), Tampa Scale of Kinesiophobia (TSK), and Comprehensive Coordination Scale (CCS) were used (α=0.82 and α=0.79, respectively). Parametric analysis of summed ordinal scores was justified by prior studies and sample size. Pearson’s and Spearman’s correlation analyses were performed using SPSS version 26.0. Results: The study found moderate motor control difficulty among participants, with a mean CCS score of 14.52 ± 3.32. Fear-related avoidance behaviors were significant (FABQ: 37.29 ± 17.32), and fear of movement was moderate to high (TSK: 31.60 ± 11.85). FABQ showed a strong positive correlation with coordination (r = 0.773, p<0.001), while TSK had a strong negative correlation (r=-0.667, p<0.001). Interestingly, FABQ and TSK were inversely correlated (r =-0.787, p<0.001), indicating distinct psychological constructs. Conclusions: Higher fear-avoidance beliefs and kinesiophobia were both associated with poorer coordination in stroke patients. Despite overlap, FABQ and TSK reflect distinct aspects of pain avoidance and fear of movement, respectively.